WORTH NOTING. (Humanist)
Focuses on items relevant to the humanist movement in the United States. Congressional threats of censorship of libraries and the Internet; Supreme Court's ruling against Colorado's Amendment 2, a anti-gay 1992 ballot proposition; Scheduled action on the Equal Opportunity Act bill by the US House of Representatives.